A method for the biological age of the heart determination - Bodretska, L. A.; Shapovalenko, I. S.; Pisaruk, A. V.; Antoniuk-Shchehlova, I. A.; Bondarenko, O. V.; Naskalova, S. S.; Shatylo, V. B. (Zaporozhye Medical Journal, 2022)
Determination of the human heart biological age (BA) is relevant for timely stratification of the risk of developing diseases, prevention, control of individual aging rate and geroprotective therapy. Aim. To study age-related changes in echocardiographic examination of the heart and to develop a formula for estimating the BA of the human heart. Materials and methods. Echocardiographic examinations of the heart were performed in 188 practically healthy people aged 30 to 79 years (73 men and 115 women), who signed an informed consent and had no clinically significant diseases in the anamnesis or at the moment. The examined were divided into age groups: I (n = 25) – 30–39 years, II (n = 40) – 40–49 years, III (n = 38) – 50–59 years, IV (n = 46) – 60–69 years, V (n = 39) – 70–79 years old. Echocardiography with Doppler in continuous-wave, pulse modes and colour mapping of flow and tissue was performed on a device Xario SSA-660A (Toshiba, Japan), sensor – PST-30BT 3.0 MHz. The state of systolic and diastolic function of the ventricles of the heart was assessed, myocardial stiffness indicators were calculated. To obtain BA formula, the calculation of the multiple linear regression equation was used based on significant features. Results. Significant increase in atrial size with age, development of diastolic dysfunction, increase in left and right ventricular myocardial infarction were found. Based on the data of the study by the method of step-by-step multiple linear regression, a formula for estimating the biological age of the human heart was obtained. The multiple correlation coefficient was a fairly high value of R = 0.847, the adjusted coefficient of determination R2 = 0.701 (F = 43.496, P ˂ 0.00001). The mean absolute error of age calculation (M ± σ) was 5.55 ± 4.24 years. The proposed formula for determining the biological age of the heart can be used for early diagnosis of accelerated aging. Conclusions. An increase in the size of the atria, the development of concentric hypertrophy of the left atrium and diastolic dysfunction, and an increase in the myocardial stiffness of the left and right ventricles of the heart, which occur with age in practically healthy people, were revealed. A formula for determining the BA of the heart with good model quality was developed using the multiple linear regression method taking into account age-related changes in the echocardiographic parameters.